1994
DOI: 10.1016/0378-1097(94)90567-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of hydrogen-utilizing bacteria in the rumen of the newborn lamb

Abstract: The development of hydrogenotrophic bacteria in the rumen of lambs was investigated by culture and labeling experiments. 14CO2 and 13CO2 incorporation by the rumen microflora of a 24-h-old lamb showed that while there was no labeled methane, double-labeled acetate was formed indicating the presence of hydrogen-dependent acetogenesis. In vitro counts from rumen fluid of 20-h-old lambs confirmed an extensive colonization of acetogenic bacteria while methanogens were absent. Methanogens appeared in the rumen of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 31 publications
1
49
0
3
Order By: Relevance
“…This suggested that consumption of the produced hydrogen is already occurring during the primary stages of development. However, this consumption is not necessarily linked to methanogenesis, as a previous study revealed the existence of a large population of hydrogenotrophic bacteria such as acetogens and sulfate‐reducing bacteria, which may compete for the hydrogen present, during early colonization (Morvan et al ., ; Fonty et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…This suggested that consumption of the produced hydrogen is already occurring during the primary stages of development. However, this consumption is not necessarily linked to methanogenesis, as a previous study revealed the existence of a large population of hydrogenotrophic bacteria such as acetogens and sulfate‐reducing bacteria, which may compete for the hydrogen present, during early colonization (Morvan et al ., ; Fonty et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Hungate's method (1969) was used to prepare media and cultivate methanogens. Media were essentially the same as previously described (Morvan et al . 1994).…”
Section: Methodsmentioning
confidence: 94%
“…The established rumen microbiome in the young animal lays a solid foundation for the transition from the pre- to the ruminant state, a critical stage for later life. Many major functional groups of ruminal microorganisms—including cellulolytic and sulfate-reducing bacteria, as well as other hydrogen-utilizing species, such as acetogenic bacteria—become established in the rumen within the first week of life [8, 36]. The role played in this experiment by the acetogenic bacteria might partly explain the different response observed in does and kids treated with BCM.…”
Section: Discussionmentioning
confidence: 99%
“…The early establishment of acetogenic bacteria underlines the competition that exists between different H 2 utilizing species within the rumen. Morvan et al [8] observed that acetogens did colonize the rumen of lambs before methanogens did. Also Faichney et al [37] reported that lambs reared in isolation from their dams produced 30–40% less methane than conventional animals and H 2 appeared to be channeled via reductive acetogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation